A simple device for collecting exhaled breath condensate (EBC) to study inflammatory biomarkers of PM10exposure in Thai schoolchildren - Waraphan Phornwisetsirikun (2018)
This study developed a portable device to collect exhaled breath condensate (EBC) and used it to collect EBC samples from schoolchildren exposed to ambient PM10. The developed device was validated, including investigating the effect of collecting duration and breathing patterns on EBC volume, with five healthy volunteers. All five volunteers tolerated the device well, completing the EBC collection procedure without difficulty. Collecting normal tidal breathing for 10 minutes yielded the required EBC volume. We conducted a follow-up study with 104 healthy schoolchildren from two different primary schools in Chiang Mai, Thailand. We measured exhaled H2O2concentrations in both the rainy and dry season; ambient PM10was significantly higher in the dry season. In the dry season, the mean exhaled H2O2concentration was significantly higher in both groups (p < 0.05). This study showed that the developed EBC collector device was cost effective, safe, rapid, and simple to use and exhaled H2O2could be used as a biomarker for elevated PM10exposure before clinical symptoms appeared.